Ethnic enclaves and labor market outcomes: What matters most: neighborhood, city or region? - Johan Klaesson; Özge Öner (Research Institute of Industrial Economics (IFN), 2018)
The relevance of residential segregation and ethnic enclaves for labor market sorting of immigrants has been investigated by a large body of literature. Previous literature presents competing arguments and mixed results for the effects of segregation and ethnic concentration on various labor market outcomes.The geographical size of the area at which segregation and/or ethnic concentration is measured, however, is left to empirical work to determine. We argue that ethnic concentration and segregation should not be used interchangeably, and more importantly, the geographical area at which they are measured relates directly to different mechanisms. We use a probabilistic approach to identify the likelihood that an immigrant is employed or a self-employed entrepreneur in the year 2005 with respect to residential segregation and ethnic concentration at the level of the neighborhood, municipality and local labor market level jointly. We study three groups of immigrants that accentuate the differences between forced and pulled migrants: (i) the first 15 member states of European Union (referred to as EU 15) and the Nordic countries, (ii) the Balkan countries, and (iii) countries in the Middle East. We find that ethnic enclaves, proxied by ethnic concentration at varying levels indicate mixed results for the different immigrant groups we study, both for their employment and entrepreneurship probability. Whereas residential segregation has a more uniformly distributed result where its relationship to any of the two labor market outcomes is almost always negative or insignificant.
Keywords: F22; O18; L26; R23; 330; Immigrant entrepreneurship; Ethnic enclaves; Segregation; Push entrepreneurship; Local labor market